A relação afetiva educativa entre o professor e o aluno como artifício facilitador do processo de ensino e aprendizagem, diálogos a parti de Henry Wallon - Santos, Dineide Sousa dos (2015)
This paper is about the educational affectionate relation between the teacher and the student as a facilitating practice in the process of teaching and learning, in the conception of the theoretician, psychologist and doctor Henry Wallon. Affection corresponds to a later period in the evolution of the child, and with the emergence of symbolic elements occurs the transformation of emotions into feelings. In this sense affection appears as a fundamental element in the human relation and in the school, and with classmates and with the teacher it is no different since both are directly involved in this process. Wallon points out that affection is at the center of the construction of knowledge and of the person. It is one of the main elements of the intelligence which can help in the development of the student. It is necessary for the teacher to deal with affection, socialization, emotional relations and the psycho-motor aspects in a playful way, aiming at recovering self-esteem and awakening interest in the child to learn and offering conditions for all involved in the process to be able to be autonomous in regard to the socially constructed knowledge. It is necessary for the teacher to know how to listen to the student and for the school to also seek innovations in its pedagogical proposals with the goal of adapting to the needs of the child, since the school represents a place of socialization, with the goal of preparing the individual for life in a permanent process of construction.